RELATIONS BETWEEN THE KAYAKING, SWIMMING AND RUNNING LIKE AN ASPECT OF THE ACTIVITIES IN THE NATURE - Milomir Trivun (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
At the sample of 24 tested male students of the Faculty of Physical Education at the University in East Sarajevo, in 2003/04 and 2004/05 who took part at the final part of the competition in kayaking, swimming and running during the mountaineering and camping like an aspect of the activities at the camp located on Tjentiste. The results of the descriptive statistic analysis point to the causality and the difference between the result's success in specific mobility abilities of the students. Specific mobility abilities showed at 200m kayaking, 100m swimming the crawl and 400m running show a great variety of the central tendency measures (minimum, maximum, mean, Std. Dev.) like the form of different stylistic ways of students' population movement.